Social and economic development and change in four Guatemalan villages: demographics, schooling, occupation, and assets - Maluccio, John; Melgar, Paul; Mendez, Humberto; Murphy, Alexis; Yount, Katherine M. (SAGE Publications, 2005)
This article uses census data and village histories to examine changes over the last 35 years in the four villages where the Institute of Nutrition of Central America and Panama (INCAP) Longitudinal Study (1969–77) was conducted and offers a rare picture of development and change in rural localities over a long period of time. In addition, by characterizing the environment in which the subjects of this study were raised, we provide context for and inputs into quantitative analyses of data collected at various points in time on these subjects. The villages have undergone massive demographic, social, and economic change. Initial differences have conditioned many of these changes, especially differences associated with agricultural potential and location. Originally these villages were rather isolated, but road and transportation access has improved substantially. The populations in the villages have more than doubled and also have aged. While marriage patterns have held steady, religious practice has changed a great deal. After many years of steady out-migration, three of the four villages are more recently experiencing net in-migration, a pattern associated with ease of access. Schooling access and outcomes also have improved, with average grades of schooling nearly tripling and literacy doubling to levels currently above national averages. Although agriculture remains an important component of individual livelihood strategies, non-agricultural sources of employment have become more important. Much of this change is associated with declining agricultural markets and increased access to non-agricultural jobs near the villages and in the capital. Accompanying these changes has been an improvement in living standards as measured by a number of indicators of household living conditions and consumer durable goods.